Sri Lankan mosaic : environment, man, continuity, and change - Swan, Bernard (Colombo, Sri Lanka : Marga Institute, Sri Lanka Centre for Development Studies, 1987)
Study covers up to early 1981.
Bibliography: p. vii-xxxii.
Keywords: Sri Lanka -- Economic conditions; Sri Lanka -- Social conditions